Tangential flow microfiltration of gasification power plant effluent using inorganic membrane - Roy, Sukumar; Agrawal, Pushpa; Mahesh Kumar, S. (2006)
In the present paper, treatment of gasification power plant effluent from gas scrubber was carried out using micro-porous alumina membrane tubes consisting of different channels (1 and 7) under simulated process conditions of temperature (45 – 55°C) and at varying transmembrane pressure drop (0.2 – 2 bar). The effect of membrane geometry on the membrane separation characteristics and fouling behavior was studied. The experimental results show that the flux decreases significantly during the first few minutes (10 min) of filtration which then stabilized with time. The decreased flux corresponds nearly to 40 %. This behavior can be attributed to the classical dependence of flux on the time in microfiltration, which shows development of a relatively important fouling layer on the membrane surface. The characteristics of the effluent after filtration displayed a very important decrease of turbidity (95%), COD (50 %), total dissolved solids (10%), total solids (55%). The total suspended solids are reduced by almost 100% and the pH remained unchanged (in the field of neutrality) during the process. The effect of various resistances that are acting in series was calculated using Darcy’s Law. These experimental results indicated that different filtration laws could be applied simultaneously for the description of the filtration data, which were found during cross-flow microfiltration of gasification power plant effluent.